Evaluating Website Performance Using EdgeOne as an Automated Web Assessment Tool - Mayang Anglingsari Putri; Dwi Astuti Aprijani; Denisha Trihapningsari; Made Diyah Putri Martinasari; Mochamad Bagoes Satria Junianto (Department of Informatics Engineering, 2026)
A university website functions not only as an information portal but also as a reflection of institutional credibility and academic reputation. Therefore, maintaining website quality—particularly web performance—is essential and must be evaluated continuously. The website of the Information Systems Study Program at Universitas Terbuka was selected as the focus of this study due to its role in delivering academic information and supporting communication with stakeholders. This research evaluates the website’s web performance using EdgeOne, an automated assessment tool that measures key performance indicators such as Time to First Byte (TTFB), First Contentful Paint (FCP), Largest Contentful Paint (LCP), Speed Index, Total Blocking Time (TBT), and Page Load Time. A descriptive quantitative approach is applied to interpret the performance metrics and identify areas requiring optimization. The results show that although the website maintains stable structural functionality, several performance indicators—particularly loading speed—remain below the recommended threshold for modern web standards. These findings highlight the importance of continuous web performance monitoring and technical optimization to improve user experience and ensure the reliability of institutional digital platforms.